Development of Portable Solar Water Purification System for Disaster Relief with IoT System - Auzini Widyasari; Nur Faiqa Binti Ismail; Satworo Adiwidodo (SM Institute, 2026)
Access to clean water remains a critical global challenge, particularly in disaster prone and rural areas where infrastructure is often damaged and electricity access is limited. This study aims to develop a portable solar powered water purification system integrated with Internet of Things technology to support emergency water supply. The system utilizes a five stage filtration process powered by a 12 V solar panel and monitored using an Arduino Uno microcontroller connected to pH, turbidity, and temperature sensors. Real time data transmission is enabled through an ESP8266 module and monitored via a mobile application platform. Performance evaluation was conducted by measuring temperature, turbidity, and pH across five filtration stages. The results indicate a significant reduction in turbidity from 724 NTU to 26 NTU and stable temperature variation within 0.4 °C, demonstrating effective particle removal and thermal consistency. However, instability was observed in the pH parameter, including an unrealistic initial reading and a final acidic value of 3.67, indicating the need for sensor recalibration and chemical stabilization. The findings suggest that integrating renewable energy, multi stage filtration, and real time monitoring provides a promising approach for portable water treatment systems, although further optimization is required to ensure drinking water safety standards in disaster relief applications.